Design of Low Power and Low Noise Instrumentation Amplifier for Biopotential Acquisition: A Review - Nahmil Koo (IEEE Access)
This paper presents a comprehensive review of amplifier design techniques for biomedical sensor implementation focusing on Capacitively Coupled Instrumentation Amplifier (CCIA). The study covers the definition of the biosignal measurement environment, examining factors that affect intrinsic noise and low noise amplifier design techniques. It analyzes the causes of input impedance reduction and explores associated boosting techniques. The sources of half-cell potential are investigated, along with DC servo loops (DSL) and methods for improving their settling time and noise performance. Through an analysis of various issues related to biopotential measurement and a state-of-the-art survey, this paper aims to provide valuable insights for the design and advancement of Instrumentation Amplifiers (IA) for IoT and biopotential measurement.